2019
DOI: 10.21462/jeltl.v4i1.184
|View full text |Cite
|
Sign up to set email alerts
|

Intercultural Communicative Competence (ICC): What Should Indonesian EFL Teachers Have Related to ICC’s Elements?

Abstract: <p><em>In the twenty-first century life, the demand to become an intercultural speaker becomes very crucial. It is seen through the incremental important attention of having an intercultural communicative competence (ICC) which is seen as one of the main key competencies in global world-wide. This condition urges any teacher to master the ICC completely as to assist their students to become intercultural speakers in multicultural situations. However, this competence has not been noticed thoroughly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Meanwhile, a plethora of studies which discuss IC have been investigated by several researchers in the Indonesian context (Abduh & Rosmaladewi, 2018;Adi, 2017;Aprianoto & Haerazi, 2019;Dollah, Syarifuddin, Abduh, Amirullah, Talib, 2017;Edi, Wello, & Dollah, 2017;Haerazi, Irwansyah, Dedi & Azis, 2018;Idris, 2020;Idris & Widyantoro, 2019;Luthfia, Rosidah, & Sofian, 2019;Miftakh, 2017;Mumu, 2017;Rosyidi & Purwati, 2018;Sabilah, 2018;Siregar, 2016;Yulianti, 2019;Zacharias, 2005); however, limited studies discussing this amid COVID-19 pandemic was found. Thus, to fill the gap of the previous related studies, it is deemed necessary to carry out a study concerning this area, i.e., challenges and opportunities encountered in intercultural language teaching, particularly during the COVID-19 pandemic based on the teachers' perspectives since they are the primary executor of the instruction conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, a plethora of studies which discuss IC have been investigated by several researchers in the Indonesian context (Abduh & Rosmaladewi, 2018;Adi, 2017;Aprianoto & Haerazi, 2019;Dollah, Syarifuddin, Abduh, Amirullah, Talib, 2017;Edi, Wello, & Dollah, 2017;Haerazi, Irwansyah, Dedi & Azis, 2018;Idris, 2020;Idris & Widyantoro, 2019;Luthfia, Rosidah, & Sofian, 2019;Miftakh, 2017;Mumu, 2017;Rosyidi & Purwati, 2018;Sabilah, 2018;Siregar, 2016;Yulianti, 2019;Zacharias, 2005); however, limited studies discussing this amid COVID-19 pandemic was found. Thus, to fill the gap of the previous related studies, it is deemed necessary to carry out a study concerning this area, i.e., challenges and opportunities encountered in intercultural language teaching, particularly during the COVID-19 pandemic based on the teachers' perspectives since they are the primary executor of the instruction conducted.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to some factors ; for instance, the rapid globalization, the unstoppedtechnology, which is increased continuously from time to time, and the globalized societies which have developed their mutual aims pertinent to the long-term economic and cultural relationships. Therefore, developing intercultural competence (henceforth IC) as one of the key competencies in 21 st -century life becomes pivotal (Delor, 1996;Idris, 2019, Sudhoff, 2010UNESCO, 2006). The common nomenclature of virtually all definitions related to IC is that it is known as a sort of concept which has gained importance in recent years (Guncavdi & Polat, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Also, it is seen as a thing which seems to be transparent, received, understood as well as utilized in the context of both formal and informal conditions (Zheng, 2014). Regarding the concept of intercultural competence , it can be defined as the ability to communicate using the target language, for example English, effectively and appropriately and be able to mingle with different people who have diverse and multicultural backgrounds of cultures, norms, and values (Byram, Gribkova, & Starkey, 2002;Idris, 2019;Setiadi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They are in the forms of technology development, globalization of the economy, widespread population migrations, the development of multiculturalism, and de-emphasis on the nations-state. Those five trends are based on the United States context, yet the three formers can be categorized as common issues which can be related to any other countries such as Indonesia (Idris, 2019). Vol 2(1), February 2021 The essential parts of the trends indicate that people are being connected rapidly and easily towards one another.…”
Section: What Is Intercultural Communicative Competence (Icc)?mentioning
confidence: 99%
“…The enhancement of intercultural communicative competence (ICC) in relation to EFL students should be taken into consideration since it has been noticed as the main aim in English language education and learning. This development of ICC can attempt to prepare and provide the EFL students with a lot of knowledge about cultural differences so that they are able to live, mingle, and be aware of their own culture as well as respect to others' cultures (Byram, 1997;Deardorff, 2006, Fantini, 2000Idris, 2019;Tran & Sheepo, 2016). The term intercultural communicative competence or in short, intercultural competence (hereafter IC) can be defined based on an individual's context (Spitzberg & Cupach, 1984).…”
Section: Introductionmentioning
confidence: 99%